2007
DOI: 10.1007/s11255-006-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of success of extracorporeal shock wave lithotripsy in the treatment of ureteric stones

Abstract: The site and transverse diameter of the stone and the presence of a ureteral stent are the only significant predictors of success of ESWL therapy for ureteric stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…A logistic regression model was designed by Abdel-Khaleketal et al [14] to predict the probability of SFR after ESWL according to three significant factors, including stone position, transverse diameter of the stone, and the presence of a ureteric stent. Salman et al [25] also reported the same three significant predictors. They found that the SFR was higher for PUS than distal US after ESWL [14,25].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…A logistic regression model was designed by Abdel-Khaleketal et al [14] to predict the probability of SFR after ESWL according to three significant factors, including stone position, transverse diameter of the stone, and the presence of a ureteric stent. Salman et al [25] also reported the same three significant predictors. They found that the SFR was higher for PUS than distal US after ESWL [14,25].…”
Section: Discussionmentioning
confidence: 70%
“…Salman et al [25] also reported the same three significant predictors. They found that the SFR was higher for PUS than distal US after ESWL [14,25]. However, the factors affecting the SFR of PUS after ESWL have not yet been defined.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Several prognostic factors determining the success of ESWL treatment of ureteric stones have been studied. These include the stone site, size, crystal type, degree of obstruction, stone impaction and function of the renal unit 2,3 . Studies of the effect of the presence of a double J stent on the ESWL success rate have given conflicting results.…”
Section: Introduction:-mentioning
confidence: 99%